The Role of Actors in Tourism Development in Tanjungpinang City, Riau Islands Province - Yuniningsih, Tri; Dwimawanti, Ida Hayu; Dyah Lituhayu (Jurnal Administrasi Publik (Public Administration Journal), 2023)
Tourism is one of the targets of the Sustainable Development Goals (SDGs). Indonesia has high tourism potential, as evidenced by the contribution of tourism to Gross Domestic Product. One area that is developing tourism is Tanjungpinang City. Tanjungpinang City is a city that has tourism characteristics by relying on Malay-Johorese culture. The number of tourist visits to Tanjungpinang City has always increased since 2017 but decreased by 89.2 percent due to the Covid-19 Pandemic. Efforts to continue to develop tourism can be done by involving various actors in tourism development. The actors involved are divided into five, namely policy creator, coordinator, implementer, facilitator, and accelerator. This study aims to determine the role of actors in tourism development in Tanjungpinang City by using a qualitative descriptive approach. The result of the research is that there are 45 actors involved. The actor is divided into five roles. Actors who act as policy creators, coordinators, and accelerators have performed their roles well. Some actors who have not played an optimal role are facilitator and implementer actors.